Does organizational culture moderate the relationship between ISO 9000 soft factors and organizational performance? - Saad, Rohaizah; Mohd Asaad, Mohd Norhasni (2014)
The aim of this paper is to examine the influence of organizational culture on the relationship between ISO 9000 soft factor and organizational performances.The inconsistent finding from published works on the relationship between ISO 9000 and organizational performance may due to organizational culture.And also there is still limited research focusing only on the soft factor of ISO 9000 and organizational performance moderated by organizational culture.This research employs item response theory (IRT) in examining the level of soft factor implementation in Malaysian automotive companies.Rasch Model analysis is adopted and the tool used to analyse data is Winstep 3.6. The finding revealed that the organizational culture is an obstacle to the relationship between the soft factor of ISO 9000 and organizational performance.In addition to that, the result also revealed that an organization with high ability in overcoming the organizational culture and resource management items especially employee empowerment and team work has a higher possibility to improve their organizational performance.